Study of Forest Floor Plant Diversity as an Indicator of Ecosystem Stability on Molosing Island, Bolaang Mongondow Regency - Ramadhan, Agung; Mokoginta, Agustinus; Arjuna, La Ode (Jurnal Biologi Tropis, 2024)
The development plan of the Bolaang Mongondow area into a new Province (Bolaang Mongondow Raya) has caused many investors to flock to the Bolaang Mongondow area, especially in Bolaang Mongondow Regency which is currently the Capital of the Regency, relying on economic growth through the industrial sector as its center will be accompanied by a decline in environmental quality because of waste products (waste) produced by the industry if not managed by the environmental impact analysis. This study aims to determine the diversity of forest floor plants as an indicator of ecosystem stability on Molosing Island, Bolaang Mongondow Regency. Data collection uses the relieve technique survey method where the plot is placed using random sampling. The results of this study will be a benchmark for the initial condition of the ecosystem in Bolaang Mongondow before the Mongondow industrial area operates. The results showed that there were 12 species of forest floor plants and a total number of individuals of 6182 individuals observed through 4 observation stations. The total value of the diversity index of Molosing Island, Bolaang Mongondow Regency is 2.473 when referring to the diversity index benchmark in the range of H'=> 1<3 which indicates that the level of diversity of forest floor plants on Molosing Island, Bolaang Mongondow Regency is in the moderate category.